2009
DOI: 10.1080/00016480902737978
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in 28 children with cochlear nerve aplasia

Abstract: Suspected congenital anomalies were confirmed by CT and MRI in all 28 children: 16 with associated labyrinthine malformations; 1 with outer, middle, and inner ear malformations; and 2 with associated monolateral facial nerve aplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 9 publications
1
32
1
1
Order By: Relevance
“…Contrary to our findings, Carner et al [15] reported on five cases of cochlear nerve aplasia in combination with an IPT2. While this might be due to different classification, this does not seem very plausible as an IPT 2 is a malformation welldefined by Mondini [16] and Sennaroglu et al [17,18].…”
Section: Discussioncontrasting
confidence: 84%
“…Contrary to our findings, Carner et al [15] reported on five cases of cochlear nerve aplasia in combination with an IPT2. While this might be due to different classification, this does not seem very plausible as an IPT 2 is a malformation welldefined by Mondini [16] and Sennaroglu et al [17,18].…”
Section: Discussioncontrasting
confidence: 84%
“…The reported prevalence of CND in children with ANSD is between 18% and 28% [10][11][12] and is higher than that in CND described in children with SNHL not distinguished as ANSD (between 6% and 16.1%). [13][14][15][16] Several studies have suggested that inner ear and brain abnormalities are common among patients with CND, 13,14,[16][17][18][19][20] but only 1 of these studies has looked specifically at patients with ANSD. In that study, substantially more patients with CND had concomitant inner ear anomalies than patients with normalappearing cochlear nerves.…”
mentioning
confidence: 99%
“…24 One shortcoming of HRCT as a single imaging modality is that it cannot identify CND in the setting of a normal caliber internal auditory canal. 6,7,[11][12][13][29][30][31] Both MRI and HRCT are important in assessing cochlear patency in children suffering from hearing loss secondary to meningitis (Fig. 4).…”
Section: Medical Assessmentmentioning
confidence: 98%